Evaluation of copper tailings from the abandoned Messina Mine for possible reuse in recreational projects, South Africa - Sphiwe Emmanuel Mhlongo; Fulufhelo Lesego Makatu; Nhlanhla Khuzulwandle Malaza; Azwihangwisi Tendani Ramalata (Journal of Degraded and Mining Lands Management, 2022)
Historic mining of copper around Musina Town left behind a sizeable unrehabilitated tailing dump. This article reports on the study conducted to investigate the suitability of using copper tailings as sand replacement in recreational projects. The methodology used involved analyzing the particle size distribution and plasticity index (PI) of the tailings and determining their particle density, bulk density, particle shape, total porosity, and permeability coefficient. The pH of the tailings, major element oxides, and heavy metals composition were all analyzed. The tailings were classified as poorly graded sand with silt (SP-SM). Low fines (9.6%) and PI (1.4) values revealed that the copper tailings were texturally suitable for application in rootzones of sports fields, courts for beach volleyball, and bunkers of the golf courses. Their particle density (2.90 g/cm³), bulk density (1.53-1.89 g/cm³), porosity (34.62-47.04%), and permeability (1.42 x 10-3 cm/sec) were all within the recommended range for application in rootzones. The angular particles of the tailings supported their uses in the bunkers. However, their pH (7.9) and high quartz content (69% SiO2) confirmed their suitability for rootzones. However, the high concentration of Cu (1872.0 mg/kg) and Cr (159.5 mg/kg) was identified as a potential risk of using the copper tailings in rootzones. This and the relatively high Al2O3 (11%) and Fe2O3 (8%) suggested that the copper tailings should be first washed or processed before being used in any recreational projects. Developing a suitable technique for processing the studied copper tailings to enhance their properties for different recreational projects was recommended.